Pengaruh Kualitas Produk dan Promosi Terhadap Keputusan Pembelian - Purwidiyantini, Ida Ayu Nyoman; Sri Hartati, Ni Putu; Mashyuni, Ida Ayu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purchasing decision is an important thing to pay attention to because this will certainly be a consideration of how a marketing strategy will be carried out by the next company.  This study aims to determine the effect of product quality and promotion on purchasing decisions at the Sea And Sun Monkey Forest Shop, Ubud.  The population in this study were all consumers of the Sea And Sun Monkey Forest Shop, Ubud and 70 respondents were taken as a sample, which was determined by the hair formula.  The sample payment method in this study used a purposive sampling method.  The data used in this study are quantitative data and qualitative data collected by observation, interviews, study documentation and questionnaires.  The analysis technique used is the Classical Assumption Test, Multiple Linear Regression Analysis, Determination Analysis, T Test and F Test. The results show that product quality has a positive and significant effect on purchasing decisions at Sea And Sun Monkey Forest Store Ubud and promotions have a positive and significant effect  on purchasing decisions at the Sea And Sun Monkey Forest Shop in Ubud.  Simultaneously product quality and promotions have a positive and significant effect on purchasing decisions at the Sea And Sun Monkey Forest Shop, Ubud